2020
DOI: 10.3389/fcell.2020.583959
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-135a Protects Against Ethanol-Induced Apoptosis in Neural Crest Cells and Craniofacial Defects in Zebrafish by Modulating the Siah1/p38/p53 Pathway

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that are involved in various biological processes, including apoptosis, by regulating gene expression. This study was designed to test the hypothesis that ethanol-induced downregulation of miR-135a contributes to ethanol-induced apoptosis in neural crest cells (NCCs) by upregulating Siah1 and activating the p38 mitogen-activated protein kinase (MAPK)/p53 pathway. We found that treatment with ethanol resulted in a significant decrease in miR-135a expression in both N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 70 publications
(94 reference statements)
0
13
0
Order By: Relevance
“…In a rat model, third trimester-equivalent ethanol exposure results in increased variance in miRNA expression and increased expression of miR-200c , a miRNA important for neurogenesis (Balaraman et al, 2017 ). In zebrafish, miR-135a is downregulated following ethanol treatment, and its overexpression reduces the associated apoptosis in neural crest cells, growth restrictions, and craniofacial defects (Yuan et al, 2020 ).…”
Section: Epigenetics: the Interface Between Genome And Environmentmentioning
confidence: 99%
“…In a rat model, third trimester-equivalent ethanol exposure results in increased variance in miRNA expression and increased expression of miR-200c , a miRNA important for neurogenesis (Balaraman et al, 2017 ). In zebrafish, miR-135a is downregulated following ethanol treatment, and its overexpression reduces the associated apoptosis in neural crest cells, growth restrictions, and craniofacial defects (Yuan et al, 2020 ).…”
Section: Epigenetics: the Interface Between Genome And Environmentmentioning
confidence: 99%
“…These results are consistent with the propensity for craniofacial defects versus the rarity of ocular anomalies in FAS. A recent study showed that miRNA-135a overexpression markedly decreased ethanol-induced apoptosis in NC cells in zebrafish embryos, and the microinjection of miRNA-135a mimics ameliorated growth retardation and craniofacial defects ( Yuan et al, 2020 ). These results suggest that microRNAs play a role in NC-mediated ocular and craniofacial development.…”
Section: Ocular Neural Crest Derivatives: Lessons From Rare Ocular DImentioning
confidence: 99%
“…In the exosomes secreted by the human diploid cell line Medical Research Council-5 (MRC-5), rabies virus infection upregulates microRNA (miR)-423-5p expression by abrogating the inhibition of cytokine signaling 3 (SOCS3) on type I interferon (IFN) signaling, resulting in feedback inhibition of RABV replication [37]. Furthermore, miR-135a family expression is downregulated to activate the p38 mitogen-activated protein kinase (MAPK)/p53 pathway, thereby contributing to apoptosis [38].…”
Section: Discussionmentioning
confidence: 99%